Borohydride‐Scaffolded Li/Na/Mg Fast Ionic Conductors for Promising Solid‐State Electrolytes. Issue 1 (10th October 2018) - Cuan, Jing; Zhou, You; Zhou, Tengfei; Ling, Shigang; Rui, Kun; Guo, Zaiping; Liu, Huakun; Yu, Xuebin
Abstract: Borohydride solid‐state electrolytes with room‐temperature ionic conductivity up to ≈70 mS cm −1 have achieved impressive progress and quickly taken their place among the superionic conductive solid‐state electrolytes. Here, the focus is on state‐of‐the‐art developments in borohydride solid‐state electrolytes, including their competitive ionic‐conductive performance, current limitations for practical applications in solid‐state batteries, and the strategies to address their problems. To open, fast Li/Na/Mg ionic conductivity in electrolytes with BH4 − groups, approaches to engineering borohydrides with enhanced ionic conductivity, and later on the superionic conductivity of polyhedral borohydrides, their correlated conductive kinetics/thermodynamics, and the theoretically predicted high conductive derivatives are discussed. Furthermore, the validity of borohydride pairing with coated oxides, sulfur, organic electrodes, MgH2, TiS2, Li4 Ti5 O12, electrode materials, etc., is surveyed in solid‐state batteries. From the viewpoint of compatible cathodes, the stable electrochemical windows of borohydride solid‐state electrolytes, the electrode/electrolyte interface behavior and battery device design, and the performance optimization of borohydride‐based solid‐state batteries are also discussed in detail. A comprehensive coverage of emerging trends in borohydride solid‐state electrolytes is provided and future maps to promote better performance of borohydride SSEs are sketched out, which will pave the way for their further development in the field of energy storage. Abstract : The borohydride family, as promising solid‐state electrolytes (SSE), is enabled by the joint advantages of superionic conductivity and good interfacial stability (with Li/Na/Mg metals). Recently, borohydride SSEs with room‐temperature ionic conductivity up to ≈70 mS cm −1 have quickly taken their place among the superionic conductive solid‐state electrolytes. The progress and future directions for borohydride‐based solid‐state batteries are systematically discussed.